Adjuvant Chemotherapy for Stage II Colon Cancer: Practice Patterns and Effectiveness in the General Population. Issue 1 (January 2017) - Booth, C.M.; Nanji, S.; Wei, X.; Peng, Y.; Biagi, J.J.; Hanna, T.P.; Krzyzanowska, M.K.; Mackillop, W.J.
Abstract: Aims: Although guidelines do not recommend adjuvant chemotherapy (ACT) for stage II colon cancer, many state that ACT may be considered in high-risk disease. Here we describe practice patterns and outcomes associated with ACT in the general population. Materials and methods: All cases of colon cancer diagnosed in Ontario 2002–2008 were identified using the Ontario Cancer Registry, which was linked to electronic treatment records. Pathology reports were obtained for a 25% random sample of cases. High-risk disease was defined as: T4 tumours, <12 lymph nodes, poorly differentiated histology, lymphovascular invasion. Modified Poisson regression was used to evaluate factors associated with ACT. The Cox proportional hazards model was used to explore the association between ACT and cancer-specific (CSS) and overall survival. Results: The study population included 2488 patients with stage II colon cancer; 1175 (47%) with high-risk disease. ACT was delivered to 18% of all patients and 24% of patients with high-risk disease. ACT rates were higher among younger patients (51% age 20–49 years versus 16% age 70–79, P  < 0.001) and varied considerably across geographic regions (range 10–39%, P  < 0.001). Among all patients with stage II colon cancer, ACT was not associated with improved CSS (hazard ratio 1.41, 95% confidence interval 1.09–1.82) or overall survival (hazard ratio 1.16, 95% confidence interval 0.94–1.42). Stratified survival analysis for patients with high-risk disease did not show benefit to ACT (CSS hazard ratio 1.14, 95% confidence interval 0.84–1.55; overall survival hazard ratio 1.02, 95% confidence interval 0.79–1.31). Conclusion: ACT use varies across age groups and geographic regions. ACT is not associated with improved survival among patients with stage II colon cancer including those with high-risk disease. Highlights: One quarter of patients with stage II colon cancer receive adjuvant chemotherapy. Chemotherapy utilisation varies widely by age and geography. Adjuvant chemotherapy is not associated with survival benefit in routine practice.